Black polyimide fiber as well as preparation method and application thereof

By using a static mixer in the spinning process, the defoamed spinning liquid and the inorganic black pigment dispersion solution are mixed, the stability and uniformity problems caused by pigment agglomeration in the stock liquid coloring technology are solved, and black polyimide fibers with high color fastness and uniformity are achieved.

CN119736729APending Publication Date: 2025-04-01JIANGSU XIANNUO NEW MATERIAL TECH

Patent Information

Application Number
CN202411928841.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the existing stock liquid coloring technology, inorganic pigments are prone to agglomeration during stand-alone defoaming, resulting in poor stability of the spinning process and poor fiber color uniformity.

Method used

The defoamed spinning liquid is mixed with the inorganic black pigment dispersion liquid by using a static mixer, and spinning directly to avoid the long-term stay of the pigment particles and possible agglomeration during standstill.

Benefits of technology

It improves the uniformity of fiber color and process stability, while retaining the advantages of high color fastness and uniform coloring in the stock solution coloring process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736729A_ABST
    Figure CN119736729A_ABST
Patent Text Reader

Abstract

The invention provides a black polyimide fiber as well as a preparation method and application thereof, the fiber comprises a black pigment, and the content of the black pigment is 0.2-8wt% of the total mass of the polyimide fiber; in the same roll of black polyimide fiber, four points are randomly selected, and the maximum color difference is less than or equal to 2. The preparation method comprises the following steps: mixing a dried inorganic black pigment with a surfactant, adding a proper amount of a solvent, carrying out ball-milling dispersion to prepare a dispersion liquid of the black pigment, respectively conveying a defoamed polyamide acid spinning solution and the dispersion liquid of the inorganic black pigment to a feeding hole of a static mixer through a pipeline under the pushing of a metering pump, and carrying out uniform stirring; the black polyimide fiber and the black polyimide fiber are mixed in a static mixer, and a wet / dry-wet spinning process is adopted to obtain the black polyimide fiber. The production process adopts stock solution coloring and has the advantages of good color uniformity and high color fastness, and the method is simple in process and low in production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance fibers, and in particular to a colored polyimide fiber and a preparation method and application thereof. Background Art

[0002] High-performance polyimide fibers have broad application prospects in aerospace, electronic power, safety protection and other fields due to their high specific strength, high specific modulus, excellent heat resistance, flame retardancy, low dielectric, and corrosion resistance. Polyimide fibers are inherently golden yellow. In order to meet the needs of different application fields, it is necessary to construct polyimide fibers of different colors. However, due to its high glass transition temperature and strong surface inertness, it is difficult to obtain colored fibers with high color fastness by using methods such as carrier dyeing and surface modification dyeing. Solution dyeing refers to the use of suitable pigments and evenly dispersing the pigments in the polyamic acid spinning solution, and spinning after sufficient mixing. Compared with carrier dyeing and surface modification dyeing methods, solution dyeing can obtain fibers with high color fastness.

[0003] Chinese patent document CN105780177A discloses a method for preparing polyimide colored silk, in which a carbon black dispersion is first prepared in a blending kettle, and then the corresponding monomers are added in sequence and at a certain molar ratio, and the carbon black dispersion is uniformly mixed with the spinning stock solution in the kettle through the stock solution circulation pipeline outside the kettle when the stock solution viscosity is controlled to be 100-1000 poise, and finally the dianhydride monomer is added and stirred for polymerization for 2-5 hours to obtain the polyamic acid spinning stock solution, and the black polyimide fiber is obtained by a dry spinning process after degassing and filtering. The production process of this invention is stock solution coloring, which has the advantage of high color fastness compared to the dyeing process, and the method is simple in process. However, in the stock solution coloring method, the suspension system composed of pigment particles and spinning solution belongs to a system that is thermodynamically and kinetically unstable. During the static degassing process after the spinning solution is mixed with carbon black, the sedimentation and agglomeration of particles in the system are inevitable, which has an adverse effect on the stability of the spinning process and the uniformity of the fiber color. Summary of the invention

[0004] In view of the above-mentioned problems existing in the prior art, the purpose of the present invention is to provide a black polyimide fiber and a preparation method thereof. The black polyimide fiber has good color uniformity. The preparation method can provide a black polyimide fiber with high process stability. The fiber has uniform color and high color fastness, and can solve the problem that inorganic pigments may agglomerate during the static degassing process in the existing stock solution coloring technology. The black polyimide fiber can be used in aerospace, high temperature protection, textile and other fields.

[0005] According to the purpose of the present invention, the present invention provides a black polyimide fiber, which contains a black pigment, and the content of the black pigment is 0.2wt%-8wt% of the total mass of the polyimide fiber; in the same roll of black polyimide fiber, four points are randomly selected, and the maximum color difference is ≤2; the physical and mechanical properties of the black polyimide fiber are: tensile strength is 0.5GPa-3.0GPa, initial modulus is 7GPa-160GPa, and color fastness to soaping is not less than level four.

[0006] In the present invention, the "black" in the black polyimide fiber can be different degrees of black, such as dark black, light black, pure black, etc., but the black polyimide fiber of the present invention has good color uniformity, that is, the same roll of black polyimide fiber presents uniform black.

[0007] In the present invention, four points are randomly selected from the same roll of black polyimide fiber, and the maximum color difference is ≤2, preferably ≤1. The color difference can be measured by conventional methods in the art. For example, four points are randomly selected from a roll of fiber, and a DS620 high-precision colorimeter is used for testing. The CIELAB value of one point is used as a reference, and the color difference between the other three points and the reference point is calculated according to the standard GB / T / 8424.3-2001. The calculation formula is:

[0008] ΔE ab * =[(L S * -L R * ) 2 +(a S * -a R * ) 2 +(b S * -b R * ) 2 ] 1 / 2

[0009] Where R and S are the CIELAB values ​​of the reference point and other points respectively.

[0010] The present invention also provides a method for preparing black polyimide fiber, which comprises the following steps:

[0011] Firstly, the dried inorganic black pigment is mixed with a surfactant, and then a proper amount of an organic solvent is added, and the mixture is ball-milled and dispersed to prepare a dispersion of the inorganic black pigment;

[0012] The degassed polyamic acid spinning solution and the inorganic black pigment dispersion are respectively transported to the feed port of the static mixer through a pipeline driven by a metering pump, and the two are mixed in the static mixer;

[0013] Then, the fiber is spun directly by a wet spinning process or a dry-wet spinning process, and the black polyimide fiber is obtained by a spinning, coagulation, drying and thermal imidization treatment.

[0014] As mentioned above, the preparation method of CN105780177A needs to be left to stand and deaerate after the synthesis. The carbon black particles may agglomerate during the standing process and cannot be dispersed again, which will clog the spinneret and affect the stability of the fiber size and the uniformity of the color. In the preparation method of the present invention, the deaeration of the spinning solution is completed first, and then the color paste and the spinning solution are evenly mixed. After the mixing is completed, there is no need to deaerate again, and spinning is directly carried out, which not only reduces the residence time of the inorganic pigment particles in the pipeline, but also does not need to be left to stand, thereby effectively reducing the agglomeration of the inorganic pigment particles, and can effectively solve the problems of poor fiber stability and poor color uniformity in the prior art, and has good color fastness.

[0015] In the present invention, preferably, the above preparation method comprises the following steps:

[0016] (1) Preparation of inorganic black pigment dispersion: After the inorganic black pigment as a colorant is dried under vacuum at 50-100° C., it is dispersed together with an appropriate amount of surfactant in an appropriate amount of organic solvent, and ground using a ball mill for 2-24 hours to prepare a dispersion having an inorganic black pigment content of 0.5 wt % to 5 wt %, which is then used for later use;

[0017] (2) Preparation of spinning solution: diamine monomer and dianhydride monomer are added to an organic solvent at a monomer molar ratio of 0.995:1-1:1.005 for synthesis, and the solid content of the solution is adjusted to 12%-20%. After the synthesis is completed, vacuum is evacuated and allowed to stand for degassing;

[0018] (3) Spinning: The degassed spinning solution and the inorganic black pigment dispersion are respectively transported to the feed port of the static mixer through a pipeline driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret for spinning by a wet method or a dry-wet method to obtain primary fibers.

[0019] (4) Drying and thermal imidization: The as-spun fibers are dried at 80°C-120°C and then imidized at 200-600°C to obtain finished fibers, i.e., black polyimide fibers.

[0020] In the preparation method of the present invention, the inorganic black pigment used as a colorant can be one or more inorganic black pigments such as carbon black, copper chrome black, iron chrome black, iron black, etc. Among them, carbon black is preferred because when carbon black is used as a colorant, cost control is convenient and the coloring effect is good and the coloring is uniform. At the same time, a surfactant is used to enhance the interaction between carbon black and polyamic acid molecules, thereby enhancing the stability of the dispersion system.

[0021] In the present invention, the organic solvent used is the solvent used in synthesizing polyamic acid (PAA), which can generally be selected from tetrahydrofuran, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, etc., preferably dimethylacetamide (DMAc).

[0022] In step (1), the content of the black inorganic pigment can be adjusted within the range of 0.5wt%-5wt%, for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%.

[0023] In step (2), the solid content can be selected within the range of 12%-20%, for example, 13%, 14%, 15%, 16%, 17%, 18%, 19%.

[0024] In the preparation method of the present invention, the commonly used diamine monomers in the art can be used, including diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), m-phenylenediamine (MPD), 2-(4-aminophenyl)-5-aminobenzimidazole (BIA), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 2,2'-dimethyl-4,4'-diaminobiphenyl (MTD), 4,4'-diaminodiphenylmethane (MDA), etc., and the commonly used dianhydride monomers can also be used, such as pyromellitic anhydride (PMDA), and the commonly used dianhydride monomers in the art can be used, including biphenyl dianhydride (BPDA), hexafluorodianhydride (6FDA), diphenyl ether tetracarboxylic dianhydride (ODPA), benzophenone tetracarboxylic dianhydride (BTDA), etc. Preferably, the diamine monomer is diaminodiphenyl ether (ODA), and the dianhydride monomer is pyromellitic anhydride (PMDA).

[0025] In addition, the static mixer used in the present invention only needs to be able to achieve the effect of static mixing, and any static mixer available in the prior art can be used.

[0026] Preferably, the content of black pigment in the black polyimide fiber is 0.2wt%-8wt% of the total weight of the polyimide fiber. When the content of black pigment is less than 0.2wt%, the fiber color cannot meet the black requirement, and when the content of black pigment is greater than 8wt%, the fiber linear density stability deteriorates. By controlling the content of black pigment to less than 8wt%, good fiber linear density stability can be achieved, and during the spinning process, the change in fiber linear density within 12 hours can be less than 2%.

[0027] Preferably, the molar ratio of the dianhydride monomer to the diamine monomer is 0.995:1-1:1.005.

[0028] More preferably, the diaminodiphenyl ether (ODA) is first added into a reactor and an appropriate amount of dimethylacetamide (DMAc) is added. After being fully mixed for more than 0.5 hour, the pyromellitic anhydride (PMDA) is weighed and slowly added into the reactor. After the addition of the materials, stirring is continued for 0.5 hour to 3 hours, and then the mixture is transferred to a spinning tank for degassing.

[0029] Through experimental testing, the physical and mechanical properties of the black polyimide fiber prepared by the method of the present invention are as follows: tensile strength is 0.5GPa-3.0GPa, initial modulus is 7GPa-160GPa, and color fastness to soaping is not less than level 4, preferably reaching level 5. In addition, in the same roll of black polyimide fiber, four points are randomly selected, and the maximum color difference is ≤2.

[0030] For polyimide fibers, there is a strong interaction between the molecules inside the fibers, which gives them excellent mechanical properties while hindering the penetration of dye molecules into the fibers. At the same time, the fiber surface lacks active groups, making it difficult to adsorb dye molecules for a long time and stably. This characteristic of being difficult to dye, coupled with the inherent golden color of the fiber itself, limits the application of polyimide fibers.

[0031] In the production process of solution-dyed fibers, by adding a black pigment dispersion and spinning after sufficient mixing, water and air pollution generated by the dyeing and finishing process can be avoided, thereby achieving the purpose of green and clean production. This method can better obtain black fibers with high coloring rate, uniform coloring, and high color fastness. At the same time, a static mixer is used to mix the spinning solution, and spinning is performed immediately after the mixing is completed, which avoids the problems of sedimentation and agglomeration of pigment particles during the long storage of the solution, and improves the stability of the process. Therefore, the method of mixing the spinning solution and the pigment with a static mixer for solution coloring and developing colored polyimide fibers can meet the needs of fiber color in different application fields.

[0032] According to another object of the present invention, on one hand, the present invention provides a black polyimide fiber, which is prepared by the above-mentioned preparation method of the black polyimide fiber.

[0033] On the other hand, the present invention provides the use of the above black polyimide fiber in the fields of aerospace, high temperature protection or textile.

[0034] In still another aspect, the present invention provides a continuous filament, a staple fiber, a woven fabric, a nonwoven fabric or a powder, which comprises the above-mentioned black polyimide fiber or the black polyimide fiber obtained by the above-mentioned preparation method.

[0035] The present invention also provides a prepreg, which comprises the black polyimide fiber or the black polyimide fiber obtained by the above preparation method.

[0036] In addition, the present invention also provides a fiber-reinforced composite material, a high-temperature protective material or a textile material, which comprises the above-mentioned continuous filaments, short fibers, woven fabrics, non-woven fabrics or powders.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) Surfactants are used to enhance the interaction between inorganic black pigment and polyamic acid molecules, thereby enhancing the stability of the dispersion system;

[0039] (2) A static mixer is used to inject the pigment into the spinning solution and mix it evenly before spinning, which can avoid the change of the properties of the spinning solution during storage and improve the fiber density stability. At the same time, the advantages of high fiber color fastness and uniform coloring in the stock solution coloring process are retained. In addition, the color of the product can be changed by simply changing the type of pigment injected into the static mixer, without the need to clean the complex pipeline, thereby reducing product loss;

[0040] (3) There is no need to change the main structure of the molecular chain, and there is no need to add additional steps in the conventional spinning process, which is conducive to reducing costs and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The figure is a schematic diagram of the preparation process of the black polyimide fiber of the present invention. DETAILED DESCRIPTION

[0042] <Fiber>

[0043] The fiber of the present invention is a polyimide fiber. As used herein, the term polyimide filament refers to a filament made of a polyimide polymer.

[0044] In some embodiments, fiber is in the form of continuous filaments. For the purpose of this paper, the term "filament" is defined as a relatively flexible, macroscopically uniform and body with a high aspect ratio on a cross section perpendicular to its length. The filament cross section can be any shape, but is typically circular. The multifilament wound onto the bobbin in a package comprises multiple continuous filaments. In the context of the present disclosure, the terms filament and fiber are used interchangeably.

[0045] Other suitable forms of fiber materials are staple fibers, wovens, nonwovens or powders, which terms are well known in the field of textile fibers.

[0046] Embodiments similar to those described above are applicable to filaments, staple fibers, wovens, nonwovens or powders.

[0047] <Composite Materials>

[0048] The black polyimide fiber of the present invention can be combined with a matrix resin to form a fiber-reinforced resin composite material. Suitable fiber forms include continuous filaments, staple fibers, woven fabrics, nonwovens or powders. The resin can be a thermosetting resin or a thermoplastic resin. Typically, the matrix resin accounts for 20% to 50% by weight of the weight of the fiber plus the resin in the composite material. Suitable thermosetting resins include epoxy resins, phenolic resins, epoxy-thermoplastic novolac resins, cyanate esters, unsaturated esters, melamine and maleimide. The fiber can be processed by any of the above methods.

[0049] Embodiments similar to those described above are applicable to fibers in filament, staple, woven, nonwoven or powder form.

[0050] The black polyimide fiber of the present invention can be combined with matrix resin to form a fiber-reinforced resin composite material. Suitable fiber forms include continuous filaments, staple fibers, woven fabrics, nonwovens or powders. Resin can be a thermosetting resin or a thermoplastic resin. Usually, in composite materials, matrix resin accounts for 20% to 50% by weight of the weight of fiber plus resin. Suitable thermosetting resins include epoxy resins, phenolic resins, epoxy-thermoplastic novolac resins, cyanate esters, unsaturated esters, melamine and maleimide etc.

[0051] The abbreviations and key terms used in the present invention are defined as follows: ODA, PDA, BPDA, PMDA, and DMAC. In the present invention, nascent fibers refer to fibers formed by polymer streams extruded from spinnerets and solidified in a spinning field, and are fibers that have not been heat-treated. Finished fibers are fibers obtained by heat-treating nascent fibers.

[0052] Figure 1The following is a schematic diagram of the preparation process of the black polyimide fiber of the present invention. Figure 1 The spinning solution and the colorant dispersion enter the static mixer through pump 1 and pump 2 respectively for mixing, and then enter the coagulation bath and the water washing bath in sequence through pump 3, and then undergo drying, thermal imidization and winding to obtain black polyimide fiber. In the present invention, a static mixer is used to inject the pigment dispersion into the spinning solution after the spinning solution is degassed and mix them evenly, which can avoid the agglomeration of pigment particles during the long-term storage of the spinning solution and improve the fiber stability, while retaining the advantages of high fiber color fastness and uniform coloring in the original solution coloring process.

[0053] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents, equipment or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0054] The fiber performance testing methods and conditions in the following examples and comparative examples are as follows:

[0055] Fiber mechanical properties: The YG001A-1 fiber electronic strength tester was used to test the tensile strength and initial modulus of the fiber.

[0056] Fiber linear density: Use YG086 yarn length measuring machine to test fiber linear density in accordance with GB / T14343-2008.

[0057] Fiber color fastness: SW-8A washing color fastness tester is used for testing in accordance with standard GB / T 3921-2008.

[0058] Color difference: Four points are randomly selected from a roll of fiber and tested using a DS620 high-precision colorimeter. The CIELAB value of one point is used as the reference. The color difference between the other three points and the reference point is calculated in accordance with standard GB / T / 8424.3-2001. The calculation formula is:

[0059] ΔE ab * =[(L S * -L R * ) 2 +(a S * -a R * ) 2 +(b S * -b R * ) 2 ] 1 / 2

[0060] Where R and S are the CIELAB values ​​of the reference point and other points respectively.

[0061] Embodiment 1:

[0062] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium dodecylbenzene sulfonate, and ball-milled for 24 hours to prepare a dispersion with a carbon black content of 5wt% for standby use. The monomers PMDA and ODA were synthesized at a molar ratio of 1:1, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, first add the diamine monomer ODA to the reactor and add an appropriate amount of DMAc, and then weigh PMDA after fully mixing for more than 0.5 hours, slowly add it to the reactor, continue stirring for 0.5 hours to 1 hour after adding the materials, and then transfer it to the spinning tank for degassing.

[0063] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 6%. The raw fiber is dried at 80°C and then subjected to gradient imidization at 240°C to 400°C to obtain the finished fiber. The carbon black accounts for 8wt% of the total mass of the polyimide fiber.

[0064] During the spinning process, the linear density of the fiber changes less than 1% within 12 hours, and the linear density stability is high. The polyimide fiber prepared in this embodiment is tested with a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber is measured to be 0.53 GPa, and the initial modulus is 8.12 GPa. The fiber color is black (RGB (22, 19, 21)), and the fiber color is uniform. Four points are randomly selected from the same roll of fiber, and the maximum color difference is 0.78, and the color fastness to soaping is level five.

[0065] Embodiment 2:

[0066] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium dodecylbenzene sulfonate, and ball-milled for 24 hours to prepare a dispersion with a carbon black content of 5wt% for standby use. The monomers BPDA and PDA were synthesized at a molar ratio of 1:1, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, the diamine monomer PDA was first added to the reactor and an appropriate amount of DMAc was added. After being fully mixed for 0.5 hours, BPDA was weighed and slowly added to the reactor. After adding the materials, stirring was continued for 1.5 hours, and then transferred to the spinning tank for degassing.

[0067] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 6%. The raw fiber is dried at 120°C and then subjected to gradient imidization at 240°C to 440°C to obtain the finished fiber. The carbon black accounts for 4wt% of the total mass of the polyimide fiber.

[0068] During the spinning process, the fiber linear density changes less than 1% within 12 hours, and the linear density stability is high. The polyimide fiber prepared in this embodiment is tested using a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber is measured to be 1.7 GPa, the initial modulus is 97 GPa, the fiber color is black (RGB (59, 61, 60)), the fiber color is uniform, and the maximum color difference of four points randomly selected from the same roll of fiber is 0.54, and the color fastness to soaping is level five.

[0069] Embodiment 3:

[0070] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium methylene dinaphthalene sulfonate, and ball-milled for 2 hours to prepare a dispersion with a carbon black content of 5wt% for standby use. The monomers BPDA and PDA were synthesized at a molar ratio of 1:1, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, the diamine monomer was first added to the reactor and an appropriate amount of DMAc was added. After being fully mixed for 0.5 hours, the dianhydride monomer was slowly added to the reactor. After adding the materials, stirring was continued for 2.5 hours, and then transferred to the spinning tank for degassing.

[0071] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 6%. The raw fiber is dried at 100°C and then subjected to gradient imidization at 260°C to 420°C to obtain the finished fiber. The carbon black accounts for 8wt% of the total mass of the polyimide fiber.

[0072] During the spinning process, the fiber linear density changes less than 2% within 12 hours, and the linear density stability is high. The polyimide fiber prepared in this embodiment is tested using a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber is measured to be 2.1 GPa, and the initial modulus is 85 GPa. The fiber color is black (RGB (38, 38, 42)), the color is uniform, and the maximum color difference of four points randomly selected from the same roll of fiber is 1.27, and the color fastness to soap washing is level five.

[0073] Embodiment 4:

[0074] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium dodecylbenzene sulfonate, and ball-milled for 24 hours to prepare a dispersion with a carbon black content of 0.5wt% for standby use. The monomers BPDA, BIA and PDA were synthesized according to a molar ratio of 10:3:7, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, the diamine monomer was first added to the reactor and an appropriate amount of DMAc was added. After being fully mixed for 0.5 hours, the dianhydride monomer was slowly added to the reactor. After adding the materials, stirring was continued for 2.5 hours, and then transferred to the spinning tank for degassing.

[0075] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 9%. The raw fiber is dried at 100°C and then subjected to gradient imidization at 240°C to 440°C to obtain the finished fiber. The carbon black accounts for 0.2wt% of the total mass of the polyimide fiber.

[0076] During the spinning process, the fiber linear density changes less than 0.5% within 12 hours, and the linear density stability is high. The polyimide fiber prepared in this embodiment is tested using a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber is measured to be 3.0 GPa, and the initial modulus is 160 GPa. The fiber color is black (RGB (69, 69, 71)), the color is uniform, and the maximum color difference of four points randomly selected from the same roll of fiber is 1.09, and the color fastness to soaping is level five.

[0077] Embodiment 5:

[0078] First, the colorant copper chrome black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium dodecylbenzene sulfonate, and ball-milled for 24 hours to prepare a dispersion with a copper chrome black content of 5wt%, which was used for standby. The monomers BPDA and PDA were synthesized at a molar ratio of 1:1, the molar ratio of amine group to anhydride group was maintained at 1:1, and the solid content of the solution was adjusted to 18%. That is, the diamine monomer PDA was first added to the reactor and an appropriate amount of DMAc was added. After being fully mixed for 0.5 hours, BPDA was weighed and slowly added to the reactor. After adding the materials, stirring was continued for 1.5 hours, and then transferred to the spinning tank for degassing.

[0079] The deaerated spinning solution and the copper chromium black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The dry-wet spinning process is used to spin the nascent fiber, wherein the coagulation bath concentration is 6%. The nascent fiber is dried at 120°C and then subjected to gradient imidization at 240°C to 440°C to obtain the finished fiber. The copper chromium black accounts for 8wt% of the total mass of the polyimide fiber.

[0080] During the spinning process, the fiber linear density changes less than 1% within 12 hours, and the linear density stability is high. The polyimide fiber prepared in this embodiment is tested using a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber is measured to be 1.6 GPa, the initial modulus is 89 GPa, the fiber color is black (RGB (60, 58, 64)), the color is uniform, and the maximum color difference of four points randomly selected from the same roll of fiber is 0.76, and the color fastness to soaping is level five.

[0081] Comparative Example 1:

[0082] First, the colorant carbon black is vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium dodecylbenzene sulfonate, and ball-milled for 24 hours to prepare a dispersion with a carbon black content of 5wt% for standby use. The monomers PMDA and ODA are synthesized at a molar ratio of 1:1, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, first add the diamine monomer ODA to the reactor and add an appropriate amount of DMAc, then add the above carbon black dispersion to the reactor, wait for 0.5 hours of full mixing, and then slowly add the dianhydride monomer PMDA to the reactor, continue stirring for 0.5-1h after adding the materials, and then transfer to the spinning tank for degassing.

[0083] The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 6%. The raw fiber is dried at 80°C, and then subjected to gradient imidization at 240°C to 400°C to obtain the finished fiber, wherein the carbon black accounts for 8wt% of the total mass of the polyimide fiber.

[0084] During the spinning process, the linear density of the fiber decreased by 15% within 8 hours, and the linear density stability was poor. The polyimide fiber prepared in this embodiment was tested with a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber was measured to be 0.55 GPa, and the initial modulus was 8.06 GPa. The fiber color was uneven, and the maximum color difference of four points randomly selected from the same roll of fiber was 4.56, and the color fastness to soaping was level five.

[0085] Comparative Example 2:

[0086] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium dodecylbenzene sulfonate, and ball-milled for 24 hours to prepare a dispersion with a carbon black content of 0.5wt% for standby use. The monomers BPDA, BIA and PDA were synthesized according to a molar ratio of 10:3:7, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, the diamine monomer was first added to the reactor and an appropriate amount of DMAc was added. After being fully mixed for 0.5 hours, the dianhydride monomer was slowly added to the reactor. After adding the materials, stirring was continued for 2.5 hours, and then transferred to the spinning tank for degassing.

[0087] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 9%. The raw fiber is dried at 100°C and then subjected to gradient imidization at 240°C to 440°C to obtain the finished fiber. The carbon black accounts for 0.1wt% of the total mass of the polyimide fiber.

[0088] During the spinning process, the fiber linear density changes less than 2% within 12 hours, and the linear density stability is high. The polyimide fiber prepared in this embodiment is tested using a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber is measured to be 2.9 GPa, and the initial modulus is 158 GPa. The fiber is dark green (RGB (19, 50, 42)), the color is uniform, and the maximum color difference of four points randomly selected from the same roll of fiber is 0.67, and the color fastness to soap washing is level five.

[0089] Comparative Example 3:

[0090] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, and then dispersed in DMAc with the surfactant sodium methylene dinaphthalene sulfonate, and ball-milled for 2 hours to prepare a dispersion with a carbon black content of 5wt% for standby use. The monomers BPDA and PDA were synthesized at a molar ratio of 1:1, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, the diamine monomer was first added to the reactor and an appropriate amount of DMAc was added. After being fully mixed for 0.5 hours, the dianhydride monomer was slowly added to the reactor. After adding the materials, stirring was continued for 2.5 hours, and then transferred to the spinning tank for degassing.

[0091] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 6%. The raw fiber is dried at 100°C and then subjected to gradient imidization at 260°C to 420°C to obtain the finished fiber. The carbon black accounts for 10wt% of the total mass of the polyimide fiber.

[0092] During the spinning process, the linear density of the fiber decreased by 15% within 12 hours, and the linear density stability was poor. The polyimide fiber prepared in this embodiment was tested using a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber was measured to be 1.8 GPa, and the initial modulus was 65 GPa. The fiber color was uneven, and the maximum color difference of four points randomly selected from the same roll of fiber was 3.28, and the color fastness to soap washing was level five.

[0093] Comparative Example 4:

[0094] First, the colorant carbon black was vacuum dried at 80°C for 24 hours, dispersed in DMAc, and ball-milled for 24 hours to prepare a dispersion with a carbon black content of 5wt% for standby use. The monomers PMDA and ODA were synthesized at a molar ratio of 1:1, maintaining the molar ratio of amine group to anhydride group at 1:1, and adjusting the solid content of the solution to 18%. That is, the diamine monomer ODA was first added to the reactor and an appropriate amount of DMAc was added. After fully mixing for 0.5 hours, PMDA was weighed and slowly added to the reactor. After adding the materials, stirring was continued for 0.5 hours to 1 hour, and then transferred to the spinning tank for degassing.

[0095] The deaerated spinning solution and the carbon black dispersion are respectively transported to the feed port of the static mixer by a pipe driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret. The wet spinning process is used to spin the raw fiber, wherein the concentration of the coagulation bath is 6%. The raw fiber is dried at 80°C and then subjected to gradient imidization at 240°C to 400°C to obtain the finished fiber. The carbon black accounts for 8wt% of the total mass of the polyimide fiber.

[0096] During the spinning process, the linear density of the fiber changed by 4% within 12 hours, and the linear density stability became worse. The polyimide fiber prepared in this embodiment was tested with a YG001A-1 fiber electronic strength meter, and the tensile strength of the fiber was measured to be 0.5 GPa, and the initial modulus was 7.90 GPa. The fiber color was uneven, and the maximum color difference of four points randomly selected from the same roll of fiber was 2.56, and the color fastness to soaping was level five.

[0097] In the above-mentioned embodiments 1 to 5, the preparation method of the black polyimide fiber of the present invention is adopted to obtain black high-performance polyimide fiber with high linear density stability. During the spinning process, the change of the fiber linear density within 12 hours is less than 2%, the color is uniform, and the maximum color difference of four points randomly taken from the same roll of fiber is ≤2.0, and the color fastness is good, and the color fastness to soaping reaches level 4 or above. In contrast, in the above-mentioned comparative example 1, carbon black is added during the synthesis of the spinning solution, and a static mixer is not used. The carbon black settles during the degassing process of the spinning solution, and the linear density decreases significantly after spinning for 8 hours, the linear density stability is poor, and the fiber color is uneven. In comparative example 2, when the amount of carbon black added is too low (the carbon black content in the fiber is less than 0.2wt%), the fiber color is dark green, which cannot meet the black requirement. In comparative example 3, when the amount of carbon black added is too high (the carbon black content in the fiber is greater than 8wt%), plate blockage is likely to occur during the spinning process, and the linear density stability is poor. In Comparative Example 4, no surfactant is added during the carbon black dispersion process, which will affect the uniformity of the carbon black dispersion in the spinning solution and deteriorate the stability of the fiber linear density.

[0098] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A black polyimide fiber, comprising a black pigment, wherein the content of the black pigment is 0.2wt%-8wt% of the total mass of the polyimide fiber; In the same roll of black polyimide fiber, four points are randomly selected, and the maximum color difference is ≤2 or ≤1; The physical and mechanical properties of the black polyimide fiber are as follows: tensile strength is 0.5 GPa-3.0 GPa, initial modulus is 7 GPa-160 GPa, and color fastness to soaping is not less than level 4 or level 5.

2. A method for preparing the black polyimide fiber according to claim 1, characterized in that: The following steps are involved: Firstly, the dried inorganic black pigment is mixed with a surfactant, and then a proper amount of an organic solvent is added, and the mixture is ball-milled and dispersed to prepare a dispersion of the inorganic black pigment; The degassed polyamic acid spinning solution and the inorganic black pigment dispersion are respectively transported to the feed port of the static mixer through a pipeline driven by a metering pump, and the two are mixed in the static mixer; The black polyimide fiber is obtained by adopting wet spinning process or dry-wet spinning process and undergoing spinning, coagulation, drying and thermal imidization treatment.

3. The method for preparing black polyimide fiber according to claim 2, wherein: The following steps are involved: (1) Preparation of inorganic black pigment dispersion: After drying the inorganic black pigment as a colorant at 50-100° C. in vacuum, disperse it together with an appropriate amount of surfactant in an appropriate amount of organic solvent, and grind it in a ball mill for 2-24 hours to prepare a dispersion having an inorganic black pigment content of 0.5 wt % to 5 wt %, which is then used for later use; (2) Preparation of spinning solution: diamine monomer and dianhydride monomer are added to an organic solvent in a molar ratio of 0.995:1-1:1.005 for synthesis, and the solid content of the solution is adjusted to 12%-20%. After the synthesis is completed, vacuum is evacuated and allowed to stand for degassing; (3) Spinning: The degassed spinning solution and the inorganic black pigment dispersion are respectively transported to the feed port of the static mixer through a pipeline driven by a metering pump. The two are mixed in the static mixer and transported to the spinneret for spinning by a wet method or a dry-wet method to obtain primary fibers. (4) Drying and thermal imidization: The as-spun fibers are dried at 80°C-120°C and then thermally imidized at 200°C-600°C to obtain finished fibers, i.e., black polyimide fibers.

4. The method for preparing black polyimide fiber according to claim 2 or 3, wherein: The inorganic black pigment is one or more selected from carbon black, copper chrome black, iron chrome black, and iron black; and / or The surfactant is one or more selected from sodium dodecylbenzene sulfonate, sodium methylene dinaphthalene sulfonate, polystyrene maleic anhydride copolymer ammonium salt, polyacrylate ammonium salt; and / or The diamine monomer is one or more selected from diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), m-phenylenediamine (MPD), 2-(4-aminophenyl)-5-aminobenzimidazole (BIA), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 2,2'-dimethyl-4,4'-diaminobiphenyl (MTD), and 4,4'-methylenediaminodiphenyl (MDA); and / or The dianhydride monomer is one or more selected from pyromellitic anhydride (PMDA), biphenyl dianhydride (BPDA), hexafluoro dianhydride (6FDA), diphenyl ether tetracarboxylic dianhydride (ODPA), and benzophenone tetracarboxylic dianhydride (BTDA).

5. The method for preparing black polyimide fiber according to claim 4, wherein: The diamine monomer is diaminodiphenyl ether (ODA), the dianhydride monomer is pyromellitic anhydride (PMDA), and the inorganic black pigment is carbon black.

6. The method for preparing black polyimide fiber according to claim 2, wherein: In the same roll of black polyimide fiber, four points are randomly selected, and the maximum color difference is ≤1; and / or The molar ratio of the dianhydride monomer to the diamine monomer is 0.995:1-1:1.005; and / or During the spinning process, the change in fiber linear density was less than 2% within 12 hours.

7. The method for preparing black polyimide fiber according to claim 2 or 3, wherein: First, add the diaminodiphenyl ether (ODA) into the reactor and add an appropriate amount of dimethylacetamide (DMAc). After being fully mixed for more than 0.5 hour, weigh the pyromellitic anhydride (PMDA) and slowly add it to the reactor. After adding the materials, continue stirring for 0.5 hour to 3 hours, and then transfer to the spinning tank for degassing.

8. Use of the black polyimide fiber according to claim 1 or the black polyimide fiber obtained by the preparation method of any one of claims 2 to 7 in the fields of aerospace, high temperature protection or textile.

9. A continuous filament, staple fiber, woven fabric, nonwoven fabric, powder or prepreg, comprising the black polyimide fiber of claim 1 or the black polyimide fiber obtained by the preparation method of any one of claims 2 to 7.

10. A fiber-reinforced composite material, high temperature protective material or textile material, comprising the continuous filament, short fiber, woven fabric, nonwoven fabric or powder according to claim 9.

Citation Information

Patent Citations

  • Method for preparing polyimide fibers

    CN102168317A

  • Method for preparing polyimide fibers

    CN104928790A

  • Polyimide superfine fiber and preparation method thereof

    CN105648567A

  • Production method of polyimide color silk

    CN105780177A

  • Preparation method of colored alginate fiber

    CN106480545A

Cited By

  • Preparation method of para-aramid colored fiber

    CN121344803A